Right to be forgotten and gender perspective. Analysis of the ruling in the Denegri case: contributions from a «romantic science» - Paola Lorenzo, Sofía (2023)
This paper aims to address the «right to be forgotten» based on the Argentinean ruling «Denegri, Natalia Ruth v. Google Inc. s/ derechos personalísimos: Acciones relacionadas» (Denegri, Natalia Ruth v. Google Inc. s/ Personal rights: Related actions), which invites us to think about whether there are ways of interpreting forgetting and constructing memory in law, and whether there is another possible way of interpreting both notions through a «romantic science» that would allow the introduction of a transdisciplinary approach in the treatment of the dramas that reach the sphere of law.